RIGID PAVEMENT PLANNING IN TRAFFIC: CASE STUDY IN CIHERANG ROAD AND PEMUDA ROAD, BOGOR REGENCY, INDONESIA - Syaiful, Syaiful; Rusfana, Hendra (Journal of Applied Engineering Science, 2022)
Rd Ciherang and Rd Pemuda, Dramaga Subdistrict, Bogor Regency, are located in a densely populated area which connects Rd Raya Dramaga and Rd Dramaga Ring. The existing condition of the road is in the form of flexible pavement or asphalt, but there are several points that have been damaged. Damage is in the form of longitudinal cracking, cracks and holes. The purpose of planning rigid pavement is to improve the surface layer of the road smoother and provide comfort, smoothness for road users. The method used is to calculate the thickness of the plate and geometric analysis of the road. The basis for choosing rigid pavement is due to its location in the mountains and poor subgrade conditions. The basic condition of rigid pavement strongly supports the movement of heavy vehicles in locations which are planned for the outer ring road. Because the geometric conditions of the road are winding and up and down, Spiral-Circle-Spiral and Full-Cyrcle planning is highly recommended. Fatik and erosion damage must be less than 100%. This is to get the results of the calculations that have been done. Rigid Pavement is planned and geometric analysis to provide comfort and smoothness for road users. In this study, a pavement thickness of 18.5cm was produced from the results of calculations using Bina Marga Method. Transverse connection using dowel diameter 25mm, length 450mm, spacing 300mm. Longitudinal connection using tie bars with a diameter of 16mm, a length of 700mm and a distance of 600mm. The results of the geometric analysis obtained five horizontal alignment forms, namely the spiral-circle-spiral (SCS) PI-1 bend with a bend length of 153.35m. The PI-2 bend is spiral-circle-spiral (SCS) with a bend length of 233.21m. The PI-3 bend is full circle (FC) type with a bend length of 174.19m. The PI-4 bend is full circle (FC) type with a bend length of 68.11m. Full circle (FC) type PI-5 bend with a bend length of 66.47m.
Keywords: road damage, rigid pavement planning, Bina Marga Method, road geometric